Obranici Unplugged - Mirković, Igor (Factum, 1999)
Duration: 00:48:00 The documentary is a story about fame without glory. Alen Vitasovic lives in the small village of Orbanici in the Croatian region of Istria. He would have an ordinary life if he had not been the most popular singer in Croatia three years ago. His huge overnight success changed Alen's life dramtically - no longer was he able to live the ordinary life of a village boy. His dreams came true, but not in the way he had imagined them.